2021
DOI: 10.3390/jcm10020261
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Knowledge on the Clinical and Methodological Aspects of Extracorporeal Shock Waves Therapy in the Management of Post-Stroke Spasticity—Overview of 20 Years of Experiences

Abstract: In many patients after stroke, spasticity develops over time, resulting in a decrease in the patient’s independence, pain, worsening mood, and, consequently, lower quality of life. In the last ten years, a rich arsenal of physical agents to reduce muscle tone such as extracorporeal shock therapy (ESWT) wave has come through. The aim of this narrative review article is to present the current state of knowledge on the use of ESWT as a supplement to the comprehensive rehabilitation of people after stroke sufferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 72 publications
2
22
0
1
Order By: Relevance
“…For reduction in post-stroke upper limb spasticity, rESWT is a promising treatment option which is safe and free of adverse side effects. The mechanism behind the action of rESWT of spastic muscle is still not clear 17 but one study was mentioned that there were a potential anti-spastic effect to regulate vasculature with rESWT 11 .…”
Section: Discussionmentioning
confidence: 99%
“…For reduction in post-stroke upper limb spasticity, rESWT is a promising treatment option which is safe and free of adverse side effects. The mechanism behind the action of rESWT of spastic muscle is still not clear 17 but one study was mentioned that there were a potential anti-spastic effect to regulate vasculature with rESWT 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, BTX is expensive and not accessible in some countries [49]. As ESWT emerged as a new non-pharmacological alternative for managing spasticity [9,10], studies comparing the effects of BTX and ESWT started to appear in the literature. Of note, some authors also reported synergistic effects when the two methods were applied concomitantly.…”
Section: Botulinum Toxin Injections and Ewstmentioning
confidence: 99%
“…In recent years, increasing evidence has been collected of extracorporeal shock wave therapy (ESWT) being a safe and effective alternative for reducing muscle spasticity. Indeed, ESWT is considered a valuable adjuvant modality to standard treatment and rehabilitation [9,10]. Accordingly, this narrative review will focus on the current evidence pertaining to the etiology, duration, and outcomes of ESWT in spasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy (ESWT) is a kind of sound wave with mechanical characteristics that generates energy through the extreme compression of the medium caused by vibration and high-speed movement ( Opara et al, 2021 ). In the past decades, the functions of ESWT in the treatment of multiple disorders has been gradually realized (non-union of long bone fracture, pain relief, tissue regeneration, neuroprotection, chondroprotection and calcified tendinopathy) ( Simplicio et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%